Relationship between hip and core muscular endurance and lower extremity injuries in division ii women`s soccer - Violett, M.; Johnson, L., Loch, J.; Hegazy, M. A. (Journal of Physical Education and Sport, 2023)
Soccer is popular worldwide and has seen recent growth in the United States, which has been associated with increased lower-extremity injuries. Recent studies have investigated the influence of core muscle endurance on sports injuries, but few studies have researched this in soccer, with none researching this influence on female player injury. The purpose of this study was to compare preseason core muscle endurance of Division II female soccer players who sustained injuries during the season to those who did not. Twenty-two female Division II soccer players (19.5 ± 1.22 years; 67.4 ± 7.42 kg; 166 ± 4.88 cm) participated in this study. Participants completed a series of four muscular endurance tests before and immediately after the season: hip abduction, hip external rotation, prone-bridge, and side-bridge. Hip abduction and external rotation tests were performed to exhaustion, with participants performing movements paced using a metronome at 30 bpm. Tests ended once participants were unable to keep pace. Static side- and prone-bridge tests ended when form could not be maintained. Independent t-tests were conducted to compare injured versus uninjured players. Eleven players sustained a lower limb sprain and/or strain injury during the season. Preseason left hip external rotator endurance and postseason right hip external rotator endurance were significantly lower in injured players (p<0.05). No other significant differences between the groups were observed. Preseason right hip external rotator endurance and post-season left hip external rotator endurance approached significance but were not statistically significant (p>0.05). Hip external rotator endurance may play a role in reducing injury in Division II women soccer athletes and therefore should be considered by coaches and athletic trainers when designing conditioning programs.